Pengaruh Penerapan Pembelajaran Media Elektronik Berbasis Role Playing Terhadap Karakter Moral Dan Agama Anak TK Saraswati 1 Denpasar - Ni Wayan Yuliani; Basilius Redan Werang; I Wayan Widiana (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determinewhether there are differences in moral and religious character of students who follow role-playing based electronic media learning and students who follow conventional learning. The population of this study is all students of Saraswati 1 Denpasar Kindergarten for the 2023/2024 school year, totaling 41 students divided into 2 classes. The sample in this study was determined by purposive sampling technique, where the entire population was used as a research sample, namely as many as 41 students divided into experimental classes and control classes. This research is a pseudo-experimental research with a non-equivalent control group design. Data on students' moral and religious character were collected using observation sheets of children's moral and religious character. Data were analyzed using ANOVA test with a significance level of 5%. The experimental results showed that the moral and religious character of students who participated in role-playing based electronic media learning was better than students who followed conventional learning. This is because students who take part in role-playing-based electronic media learning are more enthusiastic about following the learning process in class because the learning process in class is more interesting.